Lessons From the Debt Crisis: With the financial crisis still unresolved, it is worth revisiting the idea that monetary policy should concern itself only with inflation and that fiscal policy should be neutral. (Observatorio Económico, 2011)
Until the financial crash that began in 2007 with subprime mortgages in the United States –which deepened in 2008 with the failure and rescue of several financial institutions such as Bear Stearns, Lehman Brothers, and AIG– the importance assigned to financial markets within the analytical framework of  economic policy was secondary. Continue reading...
Keywords: Financial crisis